Kajian Interaksi Gajah Sumatera (Elephas Maximus Sumatranus) Dengan Masyarakat Kuyung Arang, Kabupaten Tanggamus - Dina Farida Utami; Agus Setiawan; Elly Lestari Rustiati (Jurnal Sylva Lestari, 2015)
Study on the interaction and its effects between sumateran elephants and Kuyung Arang's local people, Tanggamus was conducted in October-December 2014, direct and indirect observation, by questionnaire was applied. Amensalism is the interaction found between sumatran elephants and local people of Kuyung arang. Negative impacts include harvest fail (29.58%; n=21), crop (60.56%; n=43), and hut (9.86%; n=7) destruction. Keywords: Sumatran elephant, interaction, local people, Kuyung Arang, Bukit Barisan Selatan National Park